Opposition to “gender” in academia and beyond: How ultraconservatives and right-wing populists change the rules of the game - Korolczuk, Elżbieta (Septentrio Conference Series, 2019)
The rise of ultraconservative, often religious movements and the right-wing electoral victories in many European countries, such as Poland, limit the opportunities for inserting feminist agenda in academia, institutional settings and public debates. In my presentation I will argue that national and transnational campaigns against “gender ideology” should be interpreted a new phase of the struggle around politics of expertise and knowledge-policy nexus, highlighting issues such as the sources of scientific authorization, the status of an expert, and the ways in which the relations between academia, politics, the media and public are shaped. Right-wing populists and religious fundamentalists opposing “gender” seek not only political but also epistemic power. They attempt to build up their own sources of legitimacy, which include forming new institutions, promoting new public intellectuals and producing new body of gender knowledge. How does this increasingly hostile political context re-shape the formation and mobilization of competing gender knowledges, and how women’s movements can succeed in achieving social change?